Statistical evaluation of scientific publications in dentistry in America, in the last 25 years - Luis Fernando Restrepo Betancur (Revista Cubana de Medicina Militar)
Introduction: Scientific publications in dentistry are of interest to know the advances that occur in this area of knowledge, in order to implement them for the good of the community. Objective: To compare the scientific production and the number of citations among American countries, related to the area of dentistry in the last twenty-five years. Methods: The information was extracted from the Scimago Journal & Country Rank portal, the variables evaluated were: total number of documents, cited documents, citations, self-citations, citations per document and h-index. The statistical methods used for data processing were: MANOVA multivariate analysis of variance, multidimensional canonical contrast test, and frequency statistics. Results: A significant statistical difference was detected between nations of the American continent (p<0.05), the United States occupies the first place in the largest number of publications and citations in the time period evaluated, followed by Brazil and Canada, Honduras does not register scientific contribution in the area of dentistry. Conclusion: The topic with the least frequency of publications is oral hygiene, while the miscellany of articles related to various topics in the field of dentistry, are those with the greatest impact both in the number of citations and publications. The areas of periodontics and orthodontics present a similar pattern over time. In general, there is a large gap between the nations of Central and South America with respect to North America.